A Comparison of Higher-Order Weak Numerical Schemes for Stopped Stochastic Differential Equations (Communications in Computational Physics, 2018)
We review, implement, and compare numerical integration schemes for spatiallybounded diffusions stopped at the boundary which possess a convergence rate ofthe discretization error with respect to the time step $h$ higher than $\mathcal{O}$$(√h)$. We addressspecific implementation issues of the most general-purpose of such schemes. Theyhave been coded into a single Matlab program and compared, according to their accuracyand computational cost, on a wide range of problems in up to R48. The paper isself-contained and the code will be made freely downloadable.